Artificial Intelligence: Impact and Challenges to Authors, Journals and Medical Publishing - Peh WCG; Saw A (Malaysian Orthopaedic Journal, 2023)
Artificial intelligence (AI)-assisted technologies are here to stay and cannot be ignored. These tools are able to generate highly-realistic human-like text and perform a wide range of useful language tasks with a wide range of applications. They have the potential to expedite innovation in health care and can aid in promoting equity and diversity in research by overcoming language barriers. When using these AI tools, authors must take responsibility for the output and originality of their work, as publishers expect all content to be generated by human authors unless there is a declaration to the contrary. Authors must disclose how AI tools have been used, and ensure appropriate attribution of all the text, images, and audio-visual material. The responsible use of AI language models and transparent reporting of how these tools were used in the creation of information and publication are vital to promote and protect the credibility and integrity of medical research, and trust in medical knowledge. Educating postgraduate and undergraduate students, researchers and authors on the applications and best usage of AI-assisted technologies, together with the importance of critical thinking, integrity and strict adherence to ethical principles, are key steps that need to be undertaken.